2019
DOI: 10.1042/bsr20182232
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between miRNA target site polymorphisms in the 3′ UTR of AVPR1A and the risk of hypertension in the Chinese Han population

Abstract: We aimed to study the relationship between rs11174811 and rs3803107 single nucleotide polymorphisms (SNPs) in miRNA target sites of the 3′ UTR in the arginine vasopressin receptor 1a gene (AVPR1A) and the risk of hypertension in the Chinese Han population. The genotypes at rs11174811 and rs3803107 were analyzed by direct sequencing in 425 Chinese Han patients with hypertension and 425 healthy subjects. AVPR1A expression was investigated by transfecting miR-526b, miR-375, and miR-186 mimics into human umbilical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 24 publications
(21 reference statements)
0
6
0
Order By: Relevance
“…In particular, there are a few reports on the function of miR-375, and they suggested it to be involved in the regulation of cytokines, extracellular matrix–receptor interaction, focal adhesion, phosphatidylinositol-3 kinase-protein kinase B (Akt), amoebiasis, and protein-processing pathways [ 36 ]. Single nucleotide polymorphisms (rs11174811 and rs3803107) in miR-375 target sites of the 3′-untranslated region in the arginine vasopressin receptor 1a gene were reported to be associated with the risk of hypertension [ 37 ]. However, these studies did not indicate the involvement of miR-375 in SAS patients’ hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, there are a few reports on the function of miR-375, and they suggested it to be involved in the regulation of cytokines, extracellular matrix–receptor interaction, focal adhesion, phosphatidylinositol-3 kinase-protein kinase B (Akt), amoebiasis, and protein-processing pathways [ 36 ]. Single nucleotide polymorphisms (rs11174811 and rs3803107) in miR-375 target sites of the 3′-untranslated region in the arginine vasopressin receptor 1a gene were reported to be associated with the risk of hypertension [ 37 ]. However, these studies did not indicate the involvement of miR-375 in SAS patients’ hypertension.…”
Section: Discussionmentioning
confidence: 99%
“…Although a correlation between AVPR1A-related differences in circulating levels of AVP and emotional responses to an acute stressor was revealed ( Moons et al., 2014 ), we failed to detect any moderating effect of stressful childhood conditions on AVPR1A -related association with depression. Recently it was predicted that miR-375 and miR-186 target regions were located at the rs3803107 locus and an increased AVPR1A mRNA was detected in the case of A-allele (GA/AA genotypes) compared to GG genotypes at rs3803107 ( Zhang et al., 2019 ). In the present study we reported the association of rs3803107 A-allele and higher depression score in one ethnic group (Russians), which seems to be congruent with published data on association between lower AVPR1A level and reduced anxiety ( Barrett et al., 2013 ) and the presence of rs3803107 GG genotype ( Zhang et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently it was predicted that miR-375 and miR-186 target regions were located at the rs3803107 locus and an increased AVPR1A mRNA was detected in the case of A-allele (GA/AA genotypes) compared to GG genotypes at rs3803107 ( Zhang et al., 2019 ). In the present study we reported the association of rs3803107 A-allele and higher depression score in one ethnic group (Russians), which seems to be congruent with published data on association between lower AVPR1A level and reduced anxiety ( Barrett et al., 2013 ) and the presence of rs3803107 GG genotype ( Zhang et al., 2019 ). According to the literature, miR-375 is relevant to psychiatric conditions and psychological phenotypes ( Bhinge et al., 2016 ; Dulcis et al., 2017 ), while chronic unpredictable stress can cause miR-375 increase thus affecting expression of relevant genes ( Lotan et al., 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the gene “arginine vasopressin receptor 1A” ( AVPR1A ) is assigned to hsa -miR-584-5p. AVPR1A is expressed in peripheral blood vessels, encoding a receptor for arginine vasopressin that helps blood vessels to constrict and control blood pressure [ 28 ]. Eventually, the gene “SET domain containing 5” ( SETD5 ) is potentially targeted by hsa -miR-584-5p.…”
Section: Resultsmentioning
confidence: 99%